Building Financial Peace: A Conflict Resolution Framework for Money Arguments - Sarah D Asebedo (Journal of Financial Therapy, 2016)
This paper presents a well-known and highly utilized conflict resolution framework from the mediation profession and demonstrates how to apply this framework to money arguments. While conflict resolution skills have been identified as important to communication within the financial planning context, an integrated conflict resolution framework has yet to be recognized and understood within the financial planning literature. This paper aims to fill this gap. Ultimately, both mental health professionals and financial planners can benefit from an interdisciplinary approach to resolving money arguments by combining training in personal financial strategies and conflict resolution principles.
Keywords: Money arguments; Financial conflict; Conflict resolution; Mediation; Conflict theory